2011
DOI: 10.1345/aph.1q299
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin as an Alternative or Additive Therapy for Treatment of Pulmonary Tuberculosis

Abstract: Although it cannot be stated definitively, available evidence suggests that moxifloxacin appears to be as effective as ethambutol and is possibly as effective as isoniazid in the treatment of pulmonary TB. Given the generally poor second-line options for the treatment of TB, moxifloxacin is an attractive option as an alternative drug in TB treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…However, p- aminosalicylic acid slows down the acetylation of isoniazid in the organism, and provides a stable concentration of amantadine hydrochloride in the blood, which decreases the toxicity of isoniazid in the liver ( 11 ). Rifabutin is spiro derivative of piperidine and rifamycin; its activity against Mycobacterium tuberculosis activity is 4-fold stronger than that of the commonly clinically used drug rifampicin, and it is active against rifampicin-resistant tuberculosis ( 12 , 13 ). Amikacin, pasiniazid, pyrazinamide and propylthiouracil isonicotinoyl amine are classical anti-tuberculosis drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, p- aminosalicylic acid slows down the acetylation of isoniazid in the organism, and provides a stable concentration of amantadine hydrochloride in the blood, which decreases the toxicity of isoniazid in the liver ( 11 ). Rifabutin is spiro derivative of piperidine and rifamycin; its activity against Mycobacterium tuberculosis activity is 4-fold stronger than that of the commonly clinically used drug rifampicin, and it is active against rifampicin-resistant tuberculosis ( 12 , 13 ). Amikacin, pasiniazid, pyrazinamide and propylthiouracil isonicotinoyl amine are classical anti-tuberculosis drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that a combination of moxifloxacin, clarithromycin, and ethambutol showed therapeutic efficacy against M. avium 11 . Moreover, moxifloxacin is more effective against mycobacterial disease than older quinolone 1 12 . However, although moxifloxacin has a favorable therapeutic effect against M. avium , it is unclear whether it also has a favorable effect against M. malmoense because no studies have examined this issue.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study showed comparable activity of 400 mg of gatifloxacin, 400 mg of moxifloxacin and 1000 mg of levofloxacin, with the latter being slightly more active; at that elevated dose, ciprofloxacin was more active than ofloxacin [16,17]. Phase 2 clinical trials demonstrated that moxifloxacin versus ethambutol, isoniazid versus moxifloxacin and gatifloxacin versus ethambutol all showed a tendency to more rapid sterilisation at 8 weeks [18].…”
Section: Tuberculosismentioning
confidence: 99%